Association of A313 G polymorphism (GSTP1*B) in the glutathione-S-transferase P1 gene with sporadic Parkinson's disease - Vilar, R. (2015)
Genetic predisposition, environmental toxins and aging contribute to Parkinson's disease (PD) multifactorial etiology. Weak environmental neurotoxic factors may accumulate over time increasing the disease risk in genetically predisposed subjects. Polymorphic genes encoding drug-metabolizing-enzymes (DMEs) are considered to account for PD susceptibility by determining individual toxic response variability. In this work, the allelic distributions and genotype associations of three major brain-expressed DMEs were characterized, in sporadic PD cases and controls. No significant association was found between CYP2D6 genotype and PD, but subjects with extensive metabolizer (EM) CYP2D6 phenotype, and the variant GSTP1*B genotype were at significantly higher PD risk than the corresponding poor or intermediary metabolizers (CYP2D6 poor metabolizer phenotype+intermediary metabolizers). A significant association was observed between the GSTP1*B allele and zygosity with PD (GSTP1*A/*B - 51.58%/34.37%, odds ratio (OR) = 2.29; 95% confidence interval (95% CI) = 1.25-4.18; *B/*B - 6.32%/1.05%, OR = 10.67; 95% CI = 1.19-94.79). This association was particularly strong in the elder patients group (= 69 year) who showed double PD risk for GSTP1*B heterozygous, whilst GSTP1*B/*B homozygous were exclusively found amongst patients. An interaction between GSTM1 and GSTP1 was observed in this late onset PD group. The present results suggest that native GSTP1 encoding the fully active transferase variant should play a relevant role in dopaminergic neuroprotection.